Effect of Chinese herbal medicine injections for treatment of psoriasis vulgaris: a systematic review and meta-analysis - Li, Ziqing; Lu, Jie; Ou, Jiaxin; Yu, Jingjie; Lu, Chuanjian (Frontiers in Pharmacology, 2023)
Background: Psoriasis vulgaris (PV) is a longstanding, inflammatory, immune-responsive skin condition. For thousands of years, Chinese herbal medicine injections (CHMI) have been utilized for treating PV in Asian countries. This study aims to conduct a thorough systematic review and meta-analysis to appraise comprehensively the efficacy of CHMI in treating PV. Methods: Seven databases were searched for randomized controlled trials that evaluated the effect of CHMI in treating PV, ranging from 2004 to June 2022. The meta-analysis was undertaken based on outcome measures, treatment options, and treatment durations using Review Manager 5.4. The primary outcome measure of this study was a 60% or higher reduction in the Psoriasis Area and Severity Index score (PASI 60). A descriptive analysis was performed for the assessment of adverse events. Results: This systematic review incorporated 33 studies, comprising 3059 participants. The main findings indicate significant differences based on the PASI 60 outcome measure (RR = 1.30, 95% CI: 1.24 to 1.37, Z = 10.72, p < 0.00001), PASI 30 (RR = 1.25, 95% CI: 1.13 to 1.38, Z = 4.48, p < 0.00001), and PASI 20 (RR = 1.28, 95% CI: 1.13 to 1.45, Z = 3.82, p = 0.0001). Evaluating treatment options, CHMI in combination with monotherapies like narrow band ultraviolet B (NB-UVB) and acitretin capsule (AC), showed a greater reduction in PASI 60 (RR = 1.33, 95% CI: 1.25 to 1.43, Z = 8.32, p < 0.00001). In terms of treatment duration, no significant difference was observed when the duration extended beyond 56 days. Furthermore, the results suggested that CHMI might reduce the incidence of adverse events in the treatment of PV. Conclusion: This systematic review revealed preliminary clinical evidence supporting the use of CHMI for treating PV, considering outcome measures, treatment options, and treatment durations. However, due to the low methodological quality and limited sample size of the included studies, there is an urgent need for high-quality, multi-center, and larger-scale studies of CHMI for PV to provide robust evidence for its clinical application.